Effect of the GABA B agonist baclofen on dipyrone-induced delayed gastric emptying in rats - Collares,E.F. (2005)
Dipyrone administered intravenously (iv) or intracerebroventricularly (icv) delays gastric emptying (GE) in rats. Gamma-aminobutyric acid (GABA) is the most potent inhibitory neurotransmitter of the central nervous system. The objective of the present study was to determine the effect of icv baclofen, a GABA B receptor agonist, on delayed GE induced by dipyrone. Adult male Wistar rats received a saline test meal containing phenol red as a marker. GE was indirectly evaluated by determining the percent of gastric retention (%GR) of the meal 10 min after orogastric administration. In the first experiment, the animals were injected iv with vehicle (Civ) or 80 mg/kg (240 µmol/kg) dipyrone (Dp iv), followed by icv injection of 10 µl vehicle (bac0), or 0.5 (bac0.5), 1 (bac1) or 2 µg (bac2) baclofen. In the second experiment, the animals were injected icv with 5 µl vehicle (Cicv) or an equal volume of a solution containing 4 µmol (1333.2 µg) dipyrone (Dp icv), followed by 5 µl vehicle (bac0) or 1 µg baclofen (bac1). GE was determined 10 min after icv injection. There was no significant difference between control animals from one experiment to another concerning GR values. Baclofen at the doses of 1 and 2 µg significantly reduced mean %GR induced by iv dipyrone (Dp iv bac1 = 35.9% and Dp iv bac2 = 26.9% vs Dp iv bac0 = 51.8%). Similarly, baclofen significantly reduced the effect of dipyrone injected icv (mean %GR: Dp icv bac1 = 30.4% vs Dp icv bac0 = 54.2%). The present results suggest that dipyrone induces delayed GE through a route in the central nervous system that is blocked by the activation of GABA B receptors.